Program One Day One Egg Sebagai Strategi Pemenuhan Kebutuhan Protein Harian Anak untuk Mengurangi Angka Stunting di Desa Jetis, Kecamatan Bandungan, Kabupaten Semarang, Jawa Tengah - Insani, Galuh Adi; Suprapto, Maulina Eril; Nugroho, Khairina Paramesti; Widriati, Rendra Nandira (Direktorat Pengabdian kepada Masyarakat, 2024)
Stunting is a multifaceted and urgent issue in Indonesia. The impact of stunting extends beyond health and is also detrimental to the potential of human resources, therefore compromising the quality of future generations. Stunting is characterized by retardation in the growth of children caused by insufficient nutrition during the first 1000 days of life. Numerous food supplementation initiatives have been implemented to reduce the prevalence of stunting, including the